2022
DOI: 10.1111/imm.13466
|View full text |Cite
|
Sign up to set email alerts
|

Developing an immune‐related gene prognostic index associated with progression and providing new insights into the tumor immune microenvironment of prostate cancer

Abstract: We developed an immune‐related gene prognostic index (IGPI) associated with progression and provided new insights into the tumour immune microenvironment (TIME) for prostate cancer (PCA) patients undergoing radical prostatectomy. All analyses were conducted with R software (version 3.6.3) and its suitable packages. Meta‐analysis was performed with STATA 16.0. TUBB3, WDR62 and PPARGC1A were finally identified to establish the IGPI score. The IGPI score increased with the augment of the Gleason score and T stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…To evaluate different IRGs expression for individual patients, a quanti cation scoring model termed IRGriskscore was adopted by LASSO algorithm. Previous studies have also attempted to construct an immune-related gene prognostic index to distinguish the molecular and immune characteristics in various solid tumors [41][42][43]. For the associations of IRGriskscore with IRGcluster and IRG-genecluster, we found the IRGcluster-B and IRG-genecluster B subtype exhibited a lower IRGriskscore.…”
Section: Discussionmentioning
confidence: 74%
“…To evaluate different IRGs expression for individual patients, a quanti cation scoring model termed IRGriskscore was adopted by LASSO algorithm. Previous studies have also attempted to construct an immune-related gene prognostic index to distinguish the molecular and immune characteristics in various solid tumors [41][42][43]. For the associations of IRGriskscore with IRGcluster and IRG-genecluster, we found the IRGcluster-B and IRG-genecluster B subtype exhibited a lower IRGriskscore.…”
Section: Discussionmentioning
confidence: 74%
“…Accumulative evidence have showed that, immune microenvironment is significantly associated with tumor prognosis [42,43]. Immune cell infiltration is considered to be an indicator of the immune microenvironment within tumors [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate different IRGs expression for individual patients, a quantification scoring model termed IRGriskscore was adopted by LASSO algorithm. Previous studies have also attempted to construct an immune-related gene prognostic index to distinguish the molecular and immune characteristics in various solid tumors [ 41 , 42 , 43 ]. For the associations of IRGriskscore with IRGcluster and IRG-genecluster, we found the IRGcluster-B and IRG-genecluster B subtype exhibited a lower IRGriskscore.…”
Section: Discussionmentioning
confidence: 99%